Brazil and Bolivia by different routes - Montoya Rojas, Rodrigo (2018)
The essay traces a political and historical review of inner trends in the Latin American welfare-oriented government. On the one hand, the case of Brazil, which is undergoing severe political crisis. On the other, the Bolivia case, which faces adverse political issues, nonetheless, keeps going on the struggle to sustain and deepen the Bolivian society shifts with the commitment of social organization from El Alto and the indigenous communities.